SISTEM INFORMASI E-KASIR PADA CAFE UNICO TEMBILAHAN - Rozi, M. Sahrul; Ridha, Muh. Rasyid; Usman, Usman; Aditia, Febri (Universitas Lampung, 2024)
Currently, many cashier systems still use manual or traditional methods, which can waste customers' time, especially those in a hurry. Mistakes in calculating total expenditure can also be detrimental to restaurants and customers. Therefore, the latest innovations have made the calculation process at the cashier faster and more efficient. This information system was designed using the System Development Life Cycle (SDLC) method with the Waterfall model. The implementation uses the PHP programming language and XXAMP and MySql web servers for database management. The E-Cashier system offers many benefits for companies, such as making it easier to monitor current product data, speeding up the buying and selling process, processing financial reports at the cashier, and helping with archiving financial data. The conclusion of this research shows that E-Kasir is very useful for business people.